(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article aims to reflect on the theatrical memory of the city of Rio de Janeiro, relating the scenographic tricks of mágicas e féeries to urban transformations in the late 19th and early 20th centuries. For the analysis, the concept of theatrical allegory was approached, based on the work of Walter Benjamin and on emerging research on the historiography of hybrid theater genres. The focus was illustrated with examples of staged shows and through the sensibility of chroniclers of the time. In this way, the discussion about the erasure of urban and theatrical memory arises.